2014
DOI: 10.1186/s12929-014-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline induces TNF-alpha production and Zonula Occludens-1 redistribution in mouse Sertoli TM4 cells

Abstract: BackgroundArecoline, a major alkaloid in Areca nut has the ability to induce oxidative stress. The effect of Areca nut, arecoline on reducing sperm quality and quantity were documented previously using several animal models. Junction disruption by down-regulation of the junction-adhesive protein via oxidative stress is an important route mediating abnormal spermatogenesis. Therefore, in this present study, we investigated the functional role of arecoline on junctional proteins.ResultsTo analyze direct effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Some studies suggested the importance of TJs in the BTB, especially the ZO‐1 protein, and that TJs could regulate cytoskeletal dynamics at cell junctions and affect male fertility (Fanning & Anderson, ; Li et al, ). Kuo et al found that arecoline (a significant alkaloid in areca nut has a negative effect on male fertility) could reduce ZO‐1 protein expression, leading to the disruption of the BTB, which represented a crucial route that mediates abnormal spermatogenesis, including low sperm quantity and quality (Kuo et al, ). Besides, ZO‐1 is known to occupy a central position in the regulation of BTB dynamics as it could interact with claudins, occludin, cadherins, the actin cytoskeleton and GJs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested the importance of TJs in the BTB, especially the ZO‐1 protein, and that TJs could regulate cytoskeletal dynamics at cell junctions and affect male fertility (Fanning & Anderson, ; Li et al, ). Kuo et al found that arecoline (a significant alkaloid in areca nut has a negative effect on male fertility) could reduce ZO‐1 protein expression, leading to the disruption of the BTB, which represented a crucial route that mediates abnormal spermatogenesis, including low sperm quantity and quality (Kuo et al, ). Besides, ZO‐1 is known to occupy a central position in the regulation of BTB dynamics as it could interact with claudins, occludin, cadherins, the actin cytoskeleton and GJs.…”
Section: Discussionmentioning
confidence: 99%
“…The blood testicular barrier formed by Sertoli cells and epithelioid cells located in the seminiferous tubules creates a microenvironment that supports the process of spermatogenesis. In vitro studies have shown that arecoline can cause an impaired bloodtesticular barrier by disrupting protein that involved in tight junction formation (11). The histopathological picture of the testes in the treatment group given areca nuts showed empty tubules where there was no spermatogenesis process.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that areca nuts can cause infertility in animal trials. Administration of high doses of areca nuts can cause motility and morphology disorders of rat spermatozoa or testicular tissue abnormalities (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The primary psychoactive component of areca nuts, arecoline (Are), has been identified as a Group I human carcinogen by the International Agency for Cancer Research, 15,16 and has been shown to significantly increase the risk of oral and ECs 17,18 . Chewing areca nuts can result in the mouth conditions of oral submucous fibrosis (OSF) and oral squamous cell carcinoma (OSCC), both of which have the potential to develop into cancer 19,20 .…”
Section: Introductionmentioning
confidence: 99%